Assessment of scapular morphology and bone quality with statistical models. Issue 4 (12th March 2019) - Burton, William S.; Sintini, Irene; Chavarria, Jason M.; Brownhill, James R.; Laz, Peter J.
Abstract: The design of total shoulder arthroplasty implants are guided by anatomy. The objective of this study was to develop statistical models to quantify shape and material property variation in the scapula. Material-mapped models were reconstructed from CT scans for a training set of subjects. Statistical shape (SSM) and intensity (SIM) models were created; SSM modes described scaling, changes in the medial border and acromial process, and elongation of the scapular blade. SIM modes captured bone quality changes in the anterior and inferior glenoid. Bone quality was independent of scapular morphology. Variation described by the statistical representations can inform implant design and sizing.